2009
DOI: 10.1002/ijc.24246
|View full text |Cite
|
Sign up to set email alerts
|

Diet and upper‐aerodigestive tract cancer in Europe: The ARCAGE study

Abstract: There is suggestive, but inconclusive, evidence that dietary factors may affect risk of cancers of the upper aerodigestive tract (UADT). In the context of the alcohol-related cancers and genetic susceptibility in Europe study, we have examined the association of dietary factors with UADT cancer risk. We have analyzed data from 2,304 patients with UADT cancer and 2,227 control subjects recruited in 14 centers in 10 European countries. Dietary data were collected through a semi-quantitative food frequency questi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
47
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 71 publications
(57 citation statements)
references
References 13 publications
8
47
2
Order By: Relevance
“…The total consumption per week was summed up for all fruit and vegetable variables to get a total fruit or vegetable consumption/week variable. Frequency of fruit and vegetable consumption was categorised by country specific tertiles as low, medium and high [25]. The highest level of SP was chosen as the reference category.…”
Section: Discussionmentioning
confidence: 99%
“…The total consumption per week was summed up for all fruit and vegetable variables to get a total fruit or vegetable consumption/week variable. Frequency of fruit and vegetable consumption was categorised by country specific tertiles as low, medium and high [25]. The highest level of SP was chosen as the reference category.…”
Section: Discussionmentioning
confidence: 99%
“…The animal unsaturated fatty acids pattern emerged as mainly composed by boiled, grilled or roasted fish, steaks and lean ground beef, tinned tuna and sardines, pasta and rice with meat sauce, and fried eggs and omelettes. Although no clear indication of risk/protection emerged for milk and dairy products, meat, poultry, fish, eggs, and laryngeal cancer (6), there are suggestions that foods of animal origin and animal fats may have a detrimental effect on cancers of the upper aerodigestive tract (26)(27)(28).…”
Section: A Posteriori Dietary Patterns and Laryngeal Cancermentioning
confidence: 99%
“…Recently, Lagiou et al (2008) reported higher consumption of all examined types of red meat associated with increased UADT cancer risk, but the association was stronger for cancer of the esophagus. In particular, cold cuts displayed a 26% increased in risk for oesophageal cancer in the ARCAGE study (Lagiou et al, 2008). Not all case-control studies showed asssociation between processed meat consumption and oesophageal cancer (De Stefani et al, 1999).…”
Section: Discussionmentioning
confidence: 96%
“…A recent study in Uruguay reported an increased risk of oesophageal cancer for high intake of processed meat (De Stefani et al, 2014). Recently, Lagiou et al (2008) reported higher consumption of all examined types of red meat associated with increased UADT cancer risk, but the association was stronger for cancer of the esophagus. In particular, cold cuts displayed a 26% increased in risk for oesophageal cancer in the ARCAGE study (Lagiou et al, 2008).…”
Section: Discussionmentioning
confidence: 97%